Embedded C Programming : Techniques and Applications of C and PIC MCUS. - Siegesmund, Mark (Elsevier Science, 2014)
Quiz; Chapter 3 Preprocessor Directives; Standard Preprocessor Directives; #define id text; #include or #include "filename"; #ifdef#ifndef#else#endif#undef; #if#else#elif#endif; #error; #nolist#list; Compatibility Notes; Nonstandard Pragmas; #warning; #use delay; About Frequency; #use rs232 (options); #fuses options; #locate id=address; #byte id=x#word id=x; #bit id=x.y; #reserve address; Bootloaders; #rom address={data}; #id data; Other Pragmas; Summary; Quiz; Chapter 4 Data Variables and Types; Data Types; Characters; Integers; Compatibility Note; Integer Format.